2012 IEEE 75th Vehicular Technology Conference (VTC Spring) 2012
DOI: 10.1109/vetecs.2012.6239890
|View full text |Cite
|
Sign up to set email alerts
|

Multi-User Analog Network Coding with Spread Spectrum

Abstract: In this paper, we propose a physical layer network coding technique combined with asynchronous code division multiple access (CDMA). We consider a scenario where there are multiple pair of nodes with a single relay, and each pair of nodes exchange information asynchronously. With the assumption of asynchronous transmission, there is a trade-off between the number of nodes and the inter-user interference because the spreading codes are not orthogonal to each other. The BER and the throughput of the system are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In [154]- [156], PNC and ANC schemes have been introduced to the conventional SS systems, e.g., CDMA systems, and their error performance and throughput have been thoroughly analyzed over AWGN and multipath fading channels. The results have shown that the network-coded SS system attains a satisfactory enhancement in throughput over the conventional SS systems.…”
Section: G Network-coded Dcsk Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [154]- [156], PNC and ANC schemes have been introduced to the conventional SS systems, e.g., CDMA systems, and their error performance and throughput have been thoroughly analyzed over AWGN and multipath fading channels. The results have shown that the network-coded SS system attains a satisfactory enhancement in throughput over the conventional SS systems.…”
Section: G Network-coded Dcsk Systemsmentioning
confidence: 99%
“…In the wake of the success of network-coded CDMA systems, Kaddoum et al [70], [71] have dedicated special attention to applying the PNC and ANC techniques to DCSK-based systems. In these two papers, the authors have also analyzed the theoretical BER performance of PNC-aided DCSK system and ANC-aided DCSK system under the multipath fading condition with delay spread, which has not been considered in [154]- [156].…”
Section: G Network-coded Dcsk Systemsmentioning
confidence: 99%
“…A few other works [20]- [22] have proposed CDMA-based PNC/ANC schemes. In [20], a two-phase multiuser two-way relay network is proposed, in which multiple pairs of users communicate with their preassigned users using a common intermediate relay node.…”
Section: Related Workmentioning
confidence: 99%
“…Related Works: In [20], [21], ANC schemes for CDMA systems were proposed where each user in the system is assigned one distinct spreading sequence. To decode a message from a given user in the network, a node applies the spreading sequence of the other user.…”
Section: Introductionmentioning
confidence: 99%